Mulheres em luta: o direito à cidade na militância de mulheres em São Paulo - Mano, Natália Yukari (2018)
The purpose of this work is to study the sense of life experiences for female activists of social housing movements in the city of Sao Paulo.In order to do that, two of them shared stories that happened before they joined the social movements they are a part of now, how they feel and live the activism and what kind of city they wish to build according to the directions being followed inside these movements. We contextualize the experiences inside São Paulo, a city that works based on the neoliberal logic, founded on the capitalism and patriarchy ideals. We also assume that many factors - social class, gender and race for instance - impact the way people take ownership of urban spaces. Therefore, the urban experiences can’t and shouldn’t be treated as universals, especially if you think about planning and executing public policies. Based on that, it becomes fundamental to explore the experiences lived by women in the cities when we approach the right to city debate. We use the Social-Historic Psychology and the Feminist Epistemology as our theoretical and methodological fundamentals for the research development. The speechs built in the interviews and observations made on the field were analysed using the narrative method, whereupon we reminesce their life stories in the city, their fights and expectations for the future. With this research, we intend to make a contribution to the discussion regarding the specificities of the women activist on the right to the city and how their experiences collaborates into building a less unequal and fairer city